PEMETAAN SMK: STUDI EKSPLORATIF DI PROVINSI DIY, KALSEL, DAN KALTIM - Sudji Munadi (Jurnal Kependidikan, 2010)
This research aims to describe (1) the latest data about the existence of vocational senior high school that consists of the numbers of school, the skill program, the numbers of learning group, and the numbers of productive training teacher: (2) the comparison of the productive training teacher with the skill program and the learning group. This research was conducted by using survey technique. The population which also eshtablished as the sample of this research were all of the head of the Branch Office of Education in the provinces region Special Region of Yogyakarta (DIY), South Kalimantan, West Kalimantan, and all of the headmasters of SMK in those provinces. The data were collected by using documentation and questionnaire technique. The collected data were analyzed by using the quatitave descriptive technique and processed by SPSS 12 program. The result of this research showed that there was difference of SMK numbers between the numbers of SMK that recorded in 2008 (409 schools) and the numbers of SMK that observed in 2009. There were 423 SMKs in DIY, South Kalimantan, and East Kalimantan. 152 SMKs of them were public shool and the other 271 SMKs were private schools. The numbers of skill program were 1142 programs that located in DIY: 491, South Kalimantan: 198, and East Kalimantan: 453. The numbers of learning group = 4998 groups, for DIY 2309 groups, South Kalimantan 785 groups and East Kalimantan 1904 groups. The numbers of productive training teacher were 16069 people, DIY 7450 people, South Kalimantan 2459 people and East Kalimantan 5160 people. The comparison between teacher and skill program was 14,6 : 1, between teacher and learning group was 3,2 : 1. The skill program dominantly handled were Automotive Mechanical Engineering, Networks and Computer Technology, Accountancy, Multimedia, Marketing, and Office Administration. In addition, especially for DIY, Clothing Engineering was dominant skill program as well